EFFECTS OF SPORT-SPECIFIC STRENGTH TRAINING ON SHOT PUT AND DISCUS THROW PERFORMANCE - A. G. Jakkanagoudar; Kabadagi, Basavanneppa B (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Strength training is a fundamental component of athletic development in track and field events such as shot put and discus throw. This study examines the effects of sport-specific strength training on the performance of athletes engaged in these disciplines. A group of 30 male and female throwers were selected and divided into an experimental group, which underwent a structured strength training program, and a control group, which followed a conventional training routine. The training program included explosive strength exercises, Olympic lifts, plyometric drills, and resistance training tailored to shot put and discus throw demands. Performance metrics such as throw distance, muscular power, and biomechanical efficiency were assessed pre- and post-intervention. The results demonstrated a significant improvement in throw distances and muscular power in the experimental group compared to the control group. The findings suggest that incorporating sport-specific strength training significantly enhances performance in shot put and discus throw. This study underscores the importance of targeted strength programs in optimizing the competitive performance of throwers.